Structural asymmetry, physicochemical characterization and optical properties of a new luminescent zero dimensional organic-inorganic hybrid compound - Eya Toumi; Nour Elleuch; Sergiu Shova; Mohamed Boujelbene (Results in Chemistry)
A novel 0D organic–inorganic hybrid antimony-based halide [((R)-C8H12N)4](Sb2Cl10) was achieved through a slow evaporation method at room temperature. Single crystal X-ray diffraction analysis revealed that the compound crystallizes in the monoclinic system, within the P21 space group. The structure consists of(R)-1-phenylethylammonium (C8H12N)+cations and [Sb2Cl10]4− dimers, formed by edge-sharing distorted octahedra. The cohesion of the structure were ensured by N-H…Cl hydrogen bonds. Hirshfeld surface analysis indicated H…H interactions as the dominant intermolecular interaction contacts (42.4 %). Infrared and Raman spectroscopy confirmed the presence of organic cations and inorganic components. The thermogravimetric analysis demonstrated that the compound exhibits thermal stability up to 180 °C. Finally, Optical studies further suggest that this material holds significant promise for optical and optoelectronic applications.